The Ottawa Statement on the Ethical Design and Conduct of Cluster Randomized Trials - Weijer, Charles; Grimshaw, Jeremy M.; Eccles, Martin P.; McRae, Andrew D.; White, Angela; Brehaut, Jamie C.; Taljaard, Monica (PLoS medicine, 2012)
[...]of the unique design of CRTs, the interpretation of existing research ethics guidelines is complicated. * The Ottawa Statement on the Ethical Design and Conduct of Cluster Randomized Trials aims to provide researchers and research ethics committees (RECs) with detailed guidance on the ethical design, conduct, and review of CRTs. * A five-year mixed methods research project explored the ethical challenges of CRTs. [...]researchers and research ethics committees (RECs) currently lack specific guidelines to help them design, conduct, and review CRTs according to internationally accepted ethical standards.